The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3390/rs2071680
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Algorithm Relationships for the Estimation of the Fraction of Vegetation Cover Based on a Two Endmember Linear Mixture Model with the VI Constraint

Abstract: Measurements of the fraction of vegetation cover (FVC), retrieved from remotely sensed reflectance spectra, serves as a useful measure of land cover changes on the regional and global scales. A linear mixture model (LMM) is frequently employed to analytically estimate the FVC using the spectral vegetation index (VI) as a constraint. Variations in the application of this algorithm arise due to differences in the choice of endmember spectra and VI model assumptions. As a result, the retrieved FVCs from a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Non-linear unmixing approaches also exist (e.g., [13][14][15]), but the linear approach is used most often due to its simplicity, rationality, and feasibility in practical applications [16]. The number of spectral bands in an image limits the number of endmembers that can be used for unmixing [17], so for images with relatively few spectral bands, a common approach is to assume that FVC can be estimated by the linear combination of two endmembers: bare soil and 100% green vegetation cover [3,6,7,12,18]. In this two endmember model, it is also typically assumed that dead vegetation is spectrally-similar to bare soil [3], although [19] found that surface albedo can be used to separate soil and dead vegetation in areas with low-albedo soils.…”
Section: Introductionmentioning
confidence: 99%
“…Non-linear unmixing approaches also exist (e.g., [13][14][15]), but the linear approach is used most often due to its simplicity, rationality, and feasibility in practical applications [16]. The number of spectral bands in an image limits the number of endmembers that can be used for unmixing [17], so for images with relatively few spectral bands, a common approach is to assume that FVC can be estimated by the linear combination of two endmembers: bare soil and 100% green vegetation cover [3,6,7,12,18]. In this two endmember model, it is also typically assumed that dead vegetation is spectrally-similar to bare soil [3], although [19] found that surface albedo can be used to separate soil and dead vegetation in areas with low-albedo soils.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of endmember variable (endmember model) and constraints on the algorithms are summarized in Table 1. Below, we briefly introduce the three algorithms for the two-band case, as assumed in previous studies [28,29]. Table 1.…”
Section: Lmm-based Algorithmsmentioning
confidence: 99%
“…In these studies, a two-endmember LMM assuming two multispectral bands was used throughout to facilitate analytical derivations. Previous studies have investigated the relationship among the three types of LMM-based FVC algorithms under a two-endmember assumption [28]. Here, the relationship between FVC values derived from different algorithms is expressed analytically.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations